2017
DOI: 10.18203/2319-2003.ijbcp20173756
|View full text |Cite
|
Sign up to set email alerts
|

A study of adverse cutaneous drug reactions in the department of dermatology of a teaching hospital in Jamnagar, India

Abstract: Background: Adverse drug reactions cause significant morbidity and mortality in health care set up. They are responsible for a significant number of hospital admissions. The data for adverse cutaneous drug reactions (ACDRs) is limited our country. Thus, the present study emphasises on the need of an effective adverse drug reaction reporting programme.Methods: A prospective study to assess the ACDRs in Dermatology department was conducted in a teaching hospital of India. Male to female ratio, most common class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Variability observed in the severity of the reported cases across various studies could be due to difference in the clinical settings and the difference in speciality healthcare services provided by different hospitals. 25,37,38 It was observed that 8.62% of the reported cutaneous ADRs were probable preventable and the remaining 91.38% were not preventable and this is in accordance with a previous study. 37 As this is a retrospective analytical study, we could analyse the reactions and suspected medications as notified in the reporting form.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Variability observed in the severity of the reported cases across various studies could be due to difference in the clinical settings and the difference in speciality healthcare services provided by different hospitals. 25,37,38 It was observed that 8.62% of the reported cutaneous ADRs were probable preventable and the remaining 91.38% were not preventable and this is in accordance with a previous study. 37 As this is a retrospective analytical study, we could analyse the reactions and suspected medications as notified in the reporting form.…”
Section: Discussionsupporting
confidence: 91%
“…25,37,38 It was observed that 8.62% of the reported cutaneous ADRs were probable preventable and the remaining 91.38% were not preventable and this is in accordance with a previous study. 37 As this is a retrospective analytical study, we could analyse the reactions and suspected medications as notified in the reporting form. Information on all the concomitant medications used by patients for other conditions is lacking in few reports.…”
Section: Discussionsupporting
confidence: 91%
“…Males were found to be more affected than females in our study. This finding is in close approximation to studies done by Agrawal A et al, 10 58.1% (93) males, 41.9% (67) females), Modi A et al, 11 (55.2 % males, 44.8% females), Dhanani JG et al, 12 (54% males, 46% females), T N et al, 13 (77.7% of males, 2.3% females) and Joshi DB et al, 14 (54% males, 46% females). Similar to present study previous studies also indicate that males seem to be more susceptible than females for developing CADRs.…”
Section: Discussionsupporting
confidence: 90%
“…There were no definite or doubtful cases, which was similar by Modi et al 15 Other studies demonstrated more probable relationships with the suspected drug. 11,12,[17][18][19]22 According to modified Hartwig and Seigel scale in the current study, 78.5% and 21.5% of cutaneous reactions were mildly and moderately severe respectively. Similar results were also reported by Dhanani et al 19 Most of these patients managed by withdrawing the suspected medication and providing supportive therapy.…”
Section: Resultsmentioning
confidence: 88%
“…This is in contrast to antimicrobials (40%, 46%, 54%, 48%,), NSAIDs (35%, 18%, 23%, 30%,), and antiepileptics (8%, 10%, 11%, 12%,) in the study by Sharma et al, Modi et al, Anjaneyan et al, and Dhanani et al respectively. 12,15,16,19 Antimicrobials and NSAIDs are commonly prescribed by physicians and general practitioners, hence, higher chances of developing reactions to these groups of medications.…”
Section: Resultsmentioning
confidence: 99%